Fine-scale analysis of sea effect on coastal air temperatures at different time scales - Risto Väyrynen; Juuso Suomi; Jukka Käyhkö (Finnish Environment Institute, 2022)
We analysed the effects of the Baltic Sea on coastal temperatures in the Turku region (SW Finland) using a six-year long data series from a network of 36 temperature loggers. The sea effect was filtered from other factors with monthly linear regression models for average, daily minimum and daily maximum temperatures. The sea effect (in °C) was determined using a variable combining the shortest distance to the shoreline and the area of waterbodies within a buffer zone. The sea effect proved to be the strongest in spring and in autumn. The sea effect caused an increase in daily minimum temperatures (warming effect). Daily average temperatures also increased in summer, autumn and winter due to the sea effect; in spring however, there no such increase was recorded. Based on multiple linear regression, the maximum absolute increase in temperatures due to the sea effect occurs during night in late summer and early autumn (by ca. 2 °C), while the maximum decrease occurs in daytime in spring and early summer (by ca. 0.7 °C).